Lymphogranuloma venereum presenting as a rectovaginal fistula. - Lynch, C M (1999)
Lymphogranuloma venereum (LGV) is a rare form of the sexually transmitted disease caused by Chlamydia trachomatis. In the United States, there are fewer than 350 cases per year. In a review of the world's literature, there has not been a case reported in the last thirty years of a case of LGV presenting as a rectovaginal fistula. We present a case of an otherwise healthy American woman who presented with a rectovaginal fistula. Although uncommon, LGV does occur in developed countries and may have devastating tissue destruction if not recognized and treated before the tertiary stage.